New idea to promote the clinical applications of stem cells or their extracellular vesicles in central nervous system disorders: Combining with intranasal delivery - Yaosheng Li; Honghui Wu; Xinchi Jiang; Yunfei Dong; Juanjuan Zheng; Jianqing Gao (Elsevier, 2022)
The clinical translation of stem cells and their extracellular vesicles (EVs)-based therapy for central nervous system (CNS) diseases is booming. Nevertheless, the insufficient CNS delivery and retention together with the invasiveness of current administration routes prevent stem cells or EVs from fully exerting their clinical therapeutic potential. Intranasal (IN) delivery is a possible strategy to solve problems as IN route could circumvent the brain‒blood barrier non-invasively and fit repeated dosage regimens. Herein, we gave an overview of studies and clinical trials involved with IN route and discussed the possibility of employing IN delivery to solve problems in stem cells or EVs-based therapy. We reviewed relevant researches that combining stem cells or EVs-based therapy with IN administration and analyzed benefits brought by IN route. Finally, we proposed possible suggestions to facilitate the development of IN delivery of stem cells or EVs.